An ocean reanalysis of the western Coral Sea and Great Barrier Reef. (December 2019) - Sandery, Paul; Brassington, Gary; Colberg, Frank; Sakov, Pavel; Herzfeld, Mike; Maes, Christophe; Tuteja, Narendra
Abstract: This article describes a 10 year regional ocean reanalysis of the western Coral Sea and Great Barrier Reef (GBR) from 2006–2015. Here we use the Regional Ocean Modelling System (ROMS) at 4 km resolution and EnOI (Ensemble Optimal Interpolation) data assimilation. We also account for river freshwater discharge at the coast using hydrological stream gauge observations. The system appears to constrain features of the deep ocean circulation that are important for cross-shelf exchanges such as the spatio-temporal locations of mesoscale eddies and boundary currents. Accuracy is evaluated with forecast innovation errors respecting available observations. A four-dimensional climatological atlas of water mass properties and currents, representing 10 years of synthesis between model and data is then presented. This illustrates seasonal and climatic processes driving changes in the region, such as the El-Nino Southern Oscillation (ENSO) and its influence on sea temperature and freshwater flux to the shelf from rivers. On the shelf where dense observation coverage is limited to satellite sea surface temperature (SST), we find where SST forecast errors are low and correlations between SST and bottom temperatures are significant and take this as a reliable predictor of bottom temperatures. Differences and correlations outside these parameters suggest areas where measurement of bottom temperature is likely to be important for a long-term and comprehensive monitoring and prediction system. The reanalysis provides a realistic physical and dynamic picture of the ocean at its given resolution that may be amenable to a variety of marine and environmental studies. Highlights: Regional ocean reanalysis assimilating many available observations. Downscaled climatological atlas including effects of rivers. Baseline for regional forecast error estimates. System effectively constrains mesoscale circulation in western Coral Sea. Reliability of bottom temperature predictions investigated.